Intensification of Statin Therapy Results in a Rapid Reduction in Atherosclerotic Inflammation: Results of a Multicenter Fluorodeoxyglucose-Positron Emission Tomography/Computed Tomography Feasibility Study - TAWAKOL, Ahmed; FAYAD, Zahi A; NUNES, Irene O; BEALS, Chan R; SHANKAR, Sudha S; MOGG, Robin; ALON, Achilles; KLIMAS, Michael T; DANSKY, Hayes; SUBRAMANIAN, Sharath S; ABDELBAKY, Amr; RUDD, James H. F; et al. (Journal of the American College of Cardiology, 2013)
The study sought to test whether high-dose statin treatment would result in greater reductions in plaque inflammation than low-dose statins, using fluorodeoxyglucose-positron emission tomography/computed tomographic imaging (FDG-PET/CT). Intensification of statin therapy reduces major cardiovascular events. Adults with risk factors or with established atherosclerosis, who were not taking high-dose statins (n = 83), were randomized to atorvastatin 10 versus 80 mg in a double-blind, multicenter trial. FDG-PET/CT imaging of the ascending thoracic aorta and carotid arteries was performed at baseline, 4, and 12 weeks after randomization and target-to-background ratio (TBR) of FDG uptake within the artery wall was assessed while blinded to time points and treatment. Sixty-seven subjects completed the study, providing imaging data for analysis. At 12 weeks, inflammation (TBR) in the index vessel was significantly reduced from baseline with atorvastatin 80 mg (% reduction [95% confidence interval]: 14.42% [8.7% to 19.8%]; p < 0.001), but not atorvastatin 10 mg (% reduction: 4.2% [-2.3% to 10.4%]; p > 0.1). Atorvastatin 80 mg resulted in significant additional relative reductions in TBR versus atorvastatin 10 mg (10.6% [2.2% to 18.3%]; p = 0.01) at week 12. Reductions from baseline in TBR were seen as early as 4 weeks after randomization with atorvastatin 10 mg (6.4% reduction, p < 0.05) and 80 mg (12.5% reduction, p < 0.001). Changes in TBR did not correlate with lipid profile changes. Statin therapy produced significant rapid dose-dependent reductions in FDG uptake that may represent changes in atherosclerotic plaque inflammation. FDG-PET imaging may be useful in detecting early treatment effects in patients at risk or with established atherosclerosis.